The Juridical Implications for Refusal of Transfer of Land Rights based on The Deed of Purchase Agreement by The National Land Agency - Sundari, Tiar Novi (Jurnal Konstatering, 2022)
The sale and purchase of land rights and their registration have been determined in the UUPA and the laws and regulations under it, the existing regulations stipulate that the transfer of land rights through the sale and purchase must be with the PPAT Deed. The Sale and Purchase Deed must be immediately registered with the Land Office related to legal certainty for the new owner as the holder of the land rights. This study uses an empirical juridical research approach, used to provide a qualitative description of the juridical implications of the rejection of the transfer of land rights. The results of this study are 1) The authority regarding refusing the transfer of land rights through a sale and purchase agreement as described above is the administrative authority at BPN as regulated in Government Regulation Number 24 of 1997 concerning Land Registration. 2) The juridical implications of the rejection of the transfer of land rights through a sale and purchase agreement by the National Land Agency, namely Article 45 paragraph (2) states that if there is a refusal by the Head of the Land Office, this will be submitted in writing, including the reasons for the refusal.Keywords: Buying; Refusal; Transfer.